Perioperative selenium administration in cardiac surgery patients, a way out to reduce post surgical adversities? A meta analysis - Rehan, Syeda Tayyaba; Hussain, Hassan ul; Imran, Laiba; Eqbal, Farea; Asghar, Muhammad Sohaib (Frontiers in Cardiovascular Medicine, 2023)
Introduction The oxidative damage suffered in cardiac surgery is associated with declining trace elements which lead to the development of multi organ dysfunction (MOD), acute kidney injury (AKI), or increased length of hospital stay (LOS). Recent evidence shows the cardioprotective role of the trace element selenium as it mitigates worsening outcomes post cardiac surgery. Hence, this meta analysis aims to investigate the role of selenium in lowering cardiac surgery related adverse outcomes. Methods Literature search of five electronic databases was performed from the inception of the paper till 29th July, 2023. Eligibility criteria included; (a) randomized clinical trials with Adult patients (≥18 years) undergoing cardiac surgery (b) intervention with selenium pre or/and postoperatively; (c) a control group of a placebo, normal saline, or no selenium. Outcomes of interest include postoperative mortality, LOS in the hospital and Intensive Care Unit (ICU), AKI, troponin I, and Creatinine Kinase-MB (CK-MB). The Cochrane bias assessment tool was used to evaluate the risk of bias. Outcomes were pooled with the Mantel-Haenszel Random-effects model using Review Manager. Results Seven RCTs with 2,521 patients and 65% of males were included in this paper. No noticable differences were observed between selenium and control groups in terms of postoperative AKI, mortality, LOS in hospital and ICU, troponin I, and CK-MB levels. All studies had a low risk of bias on quality assessment. Discussion Our meta analysis demonstrated no discernible effects of selenium infusion on post operative complications among patients undergoing cardiac surgery. Further large scale multi centered studies comparing the protective role of selenium with combined therapy of other bioactive agents are needed to provide convincing explanations. Systematic Review Registration PROSPERO Identifier: 424920.